2011
DOI: 10.1111/j.1943-278x.2011.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Suicide Rates at High Altitude: Sociodemographic and Health Issues May Be to Blame

Abstract: Suicide rates are higher at high altitudes; some hypothesize that hypoxia is the cause. We examined 8,871 suicides recorded in 2006 in 15 states by the National Violent Death Reporting System, with the victim's home county altitude determined from the National Elevation Dataset through FIPS code matching. We grouped cases by altitude (low<1000m; middle=1000-1999m; high≥2000m). Of reported suicides, 5% were at high and 83% at low altitude, but unadjusted suicide rates per 100,000 population were higher at high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
(39 reference statements)
0
42
0
1
Order By: Relevance
“…Altitude of residence was a greater risk factor for suicide than the regional rate of gun ownership or population density. This finding has been independently replicated, using mortality data covering two decades (1979-1998) and 2,584 U.S. counties (Betz, Valley et al 2011; Brenner, Cheng et al 2011). We additionally found an association between altitude and depression (DelMastro, Hellem et al 2011).…”
mentioning
confidence: 76%
“…Altitude of residence was a greater risk factor for suicide than the regional rate of gun ownership or population density. This finding has been independently replicated, using mortality data covering two decades (1979-1998) and 2,584 U.S. counties (Betz, Valley et al 2011; Brenner, Cheng et al 2011). We additionally found an association between altitude and depression (DelMastro, Hellem et al 2011).…”
mentioning
confidence: 76%
“…Despite some controversies,54,55 previous epidemiological studies have consistently suggested that high altitude of residence might contribute to the increased incidence of psychiatric problems including suicide,46,56 severe psychological distress and major depressive episodes,45 and cocaine abuse 30. These phenomena are also closely associated with alterations of DA and 5-HT levels in the brain 57,58.…”
Section: Discussionmentioning
confidence: 99%
“…It was speculated that in higher altitude regions, metabolic stress with mild hypoxia might lead to a worsening of mood disorder symptoms and thus to higher suicide rates Kim et al, 2011). These findings have been criticised for not controlling for possible confounding factors such as sociodemographic variables and the availability of mental health care, alleged to be a more plausible explanation for higher suicide rates in high-altitude regions (Betz et al, 2011(Betz et al, , 2012. Nevertheless, altitude is also known to have an effect on the pharmacokinetics and has been shown to significantly influence lithium pharmacokinetics in healthy humans (Arancibia et al, 2003).…”
Section: Introductionmentioning
confidence: 99%